2020
DOI: 10.1038/s41413-019-0080-9
|View full text |Cite
|
Sign up to set email alerts
|

IgSF11 regulates osteoclast differentiation through association with the scaffold protein PSD-95

Abstract: Osteoclasts are multinucleated, giant cells derived from myeloid progenitors. While receptor activator of NF-κB ligand (RANKL) stimulation is the primary driver of osteoclast differentiation, additional signaling further contributes to osteoclast maturation. Here, we demonstrate that immunoglobulin superfamily member 11 (IgSF11), whose expression increases during osteoclast differentiation, regulates osteoclast differentiation through interaction with postsynaptic density protein 95 (PSD-95), a scaffold protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…We then performed temporal osteoclast differentiation assays in low-cell-density and high-cell-density cultures (Supplemental Figure S1B). Consistent with our previous report [14], impaired osteoclast differentiation in IgSF11 −/− cultures was observed from day 2, and the differences became bigger on day 3 in low-cell-density cultures. On the other hand, IgSF11 +/+ and IgSF11 −/− cells cultures at a high cell density showed no differences in terms of osteoclast formation.…”
Section: Impaired Osteoclast Differentiation In Igsf11-deficient Cultsupporting
confidence: 93%
See 4 more Smart Citations
“…We then performed temporal osteoclast differentiation assays in low-cell-density and high-cell-density cultures (Supplemental Figure S1B). Consistent with our previous report [14], impaired osteoclast differentiation in IgSF11 −/− cultures was observed from day 2, and the differences became bigger on day 3 in low-cell-density cultures. On the other hand, IgSF11 +/+ and IgSF11 −/− cells cultures at a high cell density showed no differences in terms of osteoclast formation.…”
Section: Impaired Osteoclast Differentiation In Igsf11-deficient Cultsupporting
confidence: 93%
“…IgSF11 has an extracellular domain with a membrane-distal V-type domain and a membrane-proximal C2-type domain, a transmembrane domain, and a cytoplasmic domain with PDZ binding motif at C-terminal. We recently demonstrated a critical role for IgSF11 in osteoclast differentiation, with IgSF11 deficiency resulting in impaired osteoclast differentiation [14]. We found that IgSF11 functions through homophilic interactions.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations